International Jurisdiction of Turkish Courts in Cases and Affairs Related to Inheritance Law - Musab Bilkay (Public and Private International Law Bulletin)
Inheritance law is one of the main branches of Turkish private law, and cases and affairs related to inheritance law are frequently seen with elements of foreignness. For this reason, it is important to determine the international jurisdiction of Turkish courts in cases and affairs (that is, non-contentious cases) related to the law of inheritance. However, the relation between Article 43 of MÖHUK (Turkish Code of International Private Law and Procedural Law), which includes the provisions outlining competent jurisdiction regarding inheritance issues, and Article 40, which is the article of general jurisdictional rules, the scope of the jurisdictional provision regarding inheritance and the nature of the jurisdiction have been the subject of considerable discussion in the doctrine. The various judicial decisions have reached different conclusions. This study will examine these issues in five sections, considering at the same time various doctrinal views and judicial decisions. Firstly, the international agreements concluded by Turkey will be examined, and then the rules of jurisdiction in the MÖHUK will be analyzed. After this part, the relationship between Article 40 and Article 43 will be considered, then, the scope of Article 43 will be clarified. Opinions and analyses about the scope of the process of issuing a certificate of inheritance will be included, and the nature of the international jurisdiction of the Turkish courts concerning the certificate of inheritance will be discussed. In the last section, the nature of the jurisdictional provision in Article 43 will be examined. Finally, this issue will be discussed together with the doctrinal views and judicial decisions.